Transformable ECM Deprivation System Effectively Suppresses Renal Cell Carcinoma by Reversing Anoikis Resistance and Increasing Chemotherapy Sensitivity (Adv. Mater. 43/2022). Issue 43 (26th October 2022) - Wang, Lu; Li, Cong; Wang, Jiaqi; Yang, Guang; Lv, Yulin; Fu, Bo; Jian, Lingrui; Ma, Jinpeng; Yu, Jiaao; Yang, Zongzheng; Wu, Peng; Li, Guangbin; et al.
Abstract : Renal Cell Carcinoma In article number 2203518, Ziqi Wang, Lei Wang, Hao Wang, Wanhai Xu, and co‐workers report a transformable extracellular matrix (ECM) deprivation system (EDS) that targets fibronectin for depriving the ECM of renal cell carcinoma (RCC). The cage‐like nanofibers formed by the EDS deprive the ECM of RCC cells, which efficaciously reverses anoikis resistance and ameliorates the RCC's cell‐adhesion‐mediated drug resistance (CAM‐DR).